2017
DOI: 10.1589/jpts.29.1689
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of physiotherapy interventions for sacroiliac joint dysfunction: a systematic review

Abstract: [Purpose] The aim of this study is to investigate the effectiveness of physical therapy interventions in the treatment of sacroiliac joint dysfunction (SIJD). [Subjects and Methods] MEDLINE, PUBMED, CINAHL, AMED, PEDro, and CIRRIE databases were searched and only relevant data from studies that matched the inclusion criteria were included. CASP tools for critical appraisal were used to assess the quality of studies included. [Results] Nine articles met the inclusion criteria, of which, three examined the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 20 publications
1
46
0
1
Order By: Relevance
“…Another study by Shinde and Jagtap [2] revealed significant improvements in the muscle energy technique (MET), hot moist pack, mulligan mobilization, and mulligan taping groups. Al-Subahi et al [5] also reported that manipulation, exercise, and �inesiotaping (�T) were ef-�inesiotaping (�T) were ef-inesiotaping (�T) were effective in treating pain, disability, and pelvic asymmetry in SIJD. Another study by Yoo [6] showed that gluteus medius strengthening exercises can help reduce SIJ pain.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Shinde and Jagtap [2] revealed significant improvements in the muscle energy technique (MET), hot moist pack, mulligan mobilization, and mulligan taping groups. Al-Subahi et al [5] also reported that manipulation, exercise, and �inesiotaping (�T) were ef-�inesiotaping (�T) were ef-inesiotaping (�T) were effective in treating pain, disability, and pelvic asymmetry in SIJD. Another study by Yoo [6] showed that gluteus medius strengthening exercises can help reduce SIJ pain.…”
Section: Introductionmentioning
confidence: 99%
“…The first line of treatment for these patients often involves referral to a physical therapist or chiropractor, whose treatment plans often include manual therapy in the form of a thrust or nonthrust manipulation, massage, or other “hands on” technique aimed at modulating pain, increasing range of motion (ROM), reducing inflammation, and/or improving tissue extensibility. A recent systematic review of intervention trials for posterior pelvic pain indicated favorable effects on pain after manual therapies . However, other reviews have been less favorable with respect to manual interventions, resulting in conflicting support for these interventions for posterior pelvic pain .…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of intervention trials for posterior pelvic pain indicated favorable effects on pain after manual therapies. 10 However, other reviews have been less favorable with respect to manual interventions, resulting in conflicting support for these interventions for posterior pelvic pain. 11 Consequently, if manual therapy is to be used in the treatment of SI joint pain, providers should understand what manual therapy may accomplish, as well as its limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, many of these muscles change function depending on whether or not the lower extremity is fixed or moving, or if the patient is in single limb or double limb stance. Therefore, proper exercise prescription and proper instruction of prescribed exercises are essential for treating posterior pelvic pain …”
mentioning
confidence: 99%
“…Therefore, proper exercise prescription and proper instruction of prescribed exercises are essential for treating posterior pelvic pain. 5,6 Finally, although strengthening exercises are necessary to ensure proper muscle function for this region, I recommend that static stretching should be used on a more limited basis. 7 Static stretching has limited ability to change muscle length and requires long hold times that may not be practical for some patients.…”
mentioning
confidence: 99%